2013
DOI: 10.1086/670052
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Increased Survival in RNA Viruses Specialized on Cancer-Derived Cells

Abstract: Viruses and other pathogens can diverge in their evolved host-use strategies because of exposure to different host types and conflicts between within-host reproduction and between-host survival. Most host-pathogen studies have emphasized the role of intrahost reproduction in the evolution of pathogen virulence, whereas the role of extra-host survival has received less attention. Here, we examine the evolution of free-living virion survival in RNA virus populations differing in their histories of host use. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…Our results show that joint consideration of different life history traits is necessary for understanding virus evolution, as shown with experimental populations of phages or wild populations of avian influenza virus (56,71,72). The consequence of the reported pleiotropic effects of resistance-breaking mutations for the evolution of resistance-breaking is a complex one.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our results show that joint consideration of different life history traits is necessary for understanding virus evolution, as shown with experimental populations of phages or wild populations of avian influenza virus (56,71,72). The consequence of the reported pleiotropic effects of resistance-breaking mutations for the evolution of resistance-breaking is a complex one.…”
Section: Discussionmentioning
confidence: 72%
“…This result is consistent with previous ones, as data on the within-host fitness of some of the CP mutants analyzed here, reported by MorenoPérez et al (25), showed no correlation with our present stability data in different susceptible hosts (not shown). To our knowledge, the relationship between survival and multiplication has not been studied for other plant viruses, but studies with bacterial or animal-infecting viruses have demonstrated that such a trade-off is not general across systems (55)(56)(57)(58)(67)(68)(69)(70)(71)(72). Trade-offs between survival and reproduction, predicted by the life history theory, need not apply for viruses, because there is no obvious mechanistic reason to expect them due to the differences between the extracellular and intracellular environments where survival and reproduction, respectively, occur, as pointed out by Goldhill and Turner (19).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many types of abiotic perturbations can cause viral mortality, i.e., the inability of a viral particle to successfully complete within-host replication after experiencing an environmental challenge (56). A wide variety of environmental stressors are known to somehow compromise a virus's subsequent ability to productively infect a host; examples include changes in ambient temperature, ionic strength (saltiness), UV radiation, acidity, atmospheric pressure, and moisture (2,49,56,58). Although capsids function to protect viral nucleic acid from degradation by these and other environmental stressors, the protection is not absolute, and some viruses may experience very short half-lives outside of the host under these harsh conditions.…”
Section: Biotic and Abiotic Challenges Faced By Virusesmentioning
confidence: 99%
“…Infectious viruses are nonmetabolizing microbes, which do not experience the metabolic trade‐offs sometimes suffered by cellular organisms. But it is evident that viruses experience life‐history compromises analogous to those observed in evolving populations of cellular life forms (e.g., De Paepe and Taddei ; Ogbunugafor et al ). The proteins and hereditary nucleic acids (RNA or DNA) of infectious virus particles may be easily degraded by extra‐host environmental stressors, such as extremes in temperature and pH.…”
mentioning
confidence: 99%
“…The study showed that selection strictly on cancer cells led to increased extracellular survival of VSV populations, attributed to relatively faster cell‐to‐cell spread of viruses on cancer cells and the more rapid senescence of these cell types, either of which may select for enhanced virus stability between host‐cell replenishment. However, Ogbunugafor et al () showed only weak evidence that increased virion survival coincided with decreased intrahost reproduction, and this outcome was confounded by cell type (i.e., it was not observed across all host treatments), preventing the possibility of drawing general conclusions on evolved survival/reproduction trade‐offs in VSV.…”
mentioning
confidence: 99%